An Empirical Study on Compensation Management Practices in Digital Marketing Company (International Journal of Scientific Research and Management (IJSRM), 2022)
Compensation management is often referred as salary and wage administration. Human resource management department designs compensation policy. Organizations can be competitive if they update their compensation package according to market conditions. Standard human resource policy gives high priority for better compensation package. The parameters considered while designing compensation management are job responsibilities, experience, company budget and job market. Human resource managers design compensation strategy through scorecard. Pay equity can be attained with competitive compensation package. The research was conducted to the employee working in Hyderabad digital marketing companies. The hypotheses were tested using chi square test, ANOVA & other statistical testing tools.